The Role of Microbiota in Cancer Therapy - Perez-Chanona, Ernesto (Curr Opin Immunol, 2016)
The relationship between the host and the commensal microbiota regulates physiological functions including inflammation and immunity and it has been scrutinized in the context of cancer. While viruses and bacterial species have been implicated in oncogenesis, commensal microbes also have a beneficial role in the fight against cancer. Therapy efficacy, including adoptive T cell transfer, alkylating agents and immune checkpoint blockers, relies on immunity that receives its education from the gut microbiota. In cancer therapy with immunostimulating oligonucleotides and platinum salts, the microbiota also modulates the response by priming for the release of pro-inflammatory factors and reactive oxygen species, respectively. This new information offers promising clinical possibilities of modulating cancer therapy and its toxic side effects by targeting the microbiota.